Różne marginesy - Artwich, Anna (Przestrzenie Teorii, 2023)
The article contains a review of bell hooks’ Feminist Theory: From Margin to Center (1984; Wydawnictwo Krytyki Politycznej, Warszawa 2013, second edition 2022). The text by the American scholar presents groundbreaking theses for the development of the Black feminism movement – she was one of the first to draw attention to the need to take into account various social determinants of violence against women. At the same time, it emphasizes the exclusionary and marginalizing assumptions of second-wave feminism that dominated in the mid-twentieth century. In my review, I reflect on the importance of republishing a theoretical book that examines the systemic violence faced by Black women in a patriarchal and white society. For me, it is important to ask about the relevance of hooks’ reflections and the role they play in thinking about feminism in contemporary capitalist society. I also reflect on the applicability of hooks’ theory in Polish feminism context.